2018
DOI: 10.1002/aocs.12053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Physical Properties, and the Oxidative Stability of Oil Bodies Extracted From Argania spinosa

Abstract: Oil bodies (OB) were extracted from argan kernels using an aqueous extraction method. The composition of OB revealed its lipid profile, which had a high content of stearic and palmitic acid. Besides, evidence suggested an association between OB and tocopherols. The physical properties of argan OB (AOB) showed that their size was around 1.9 μm and the ζ-potential went from +17.7 mV at pH 2.0 to −32.25 mV at pH 8, with an isoelectric point around pH 5.1. OB were stable and small at pH 2.0, 7.0, and 8.0 but large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…It is widely evidenced that argan oil is an important food. It is prepared from roasted argan kernels, whose pressing can be performed using traditional and modern techniques (14)(15)(16). In both cases, the obtained argan oil has a golden color and a unique hazelnut taste (17).…”
Section: Importance Of Argan Oil As a Food And Cosmetic Productmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely evidenced that argan oil is an important food. It is prepared from roasted argan kernels, whose pressing can be performed using traditional and modern techniques (14)(15)(16). In both cases, the obtained argan oil has a golden color and a unique hazelnut taste (17).…”
Section: Importance Of Argan Oil As a Food And Cosmetic Productmentioning
confidence: 99%
“…There are two kinds of argan oils in the market, namely, food argan oil and beauty (cosmetic) use (name INCI: Argania spinosa kernel oil) (21). This is a cold pressed oil, however, it is obtained from unroasted argan kernels (15,22). Cosmetic argan oil is intended to be applied directly to the skin or hair, or to be an ingredient in other cosmetic preparations (21,23,24).…”
Section: Importance Of Argan Oil As a Food And Cosmetic Productmentioning
confidence: 99%
See 1 more Smart Citation
“…But temperature may affect the stability of the OB from another aspect. Previous studies have found that endogenous enzymes such as proteases and phospholipases are present in oil bodies, and the degradation of enzymes during storage of oil bodies also affects the stability of oil bodies 45,46 . Moreover, temperature fluctuations are unavoidable in the actual application of the OB, which will lead to changes in enzyme activity and thus affect the stability of the OB.…”
Section: As Shown Inmentioning
confidence: 99%
“…These different virtues and benefits of argan oil could be attributed to its richness in tocopherols, unsaturated fatty acids (oleic acid), and phenolic compounds (Marfil et al, 2011). The chemical composition of the argan oil is essentially formed by two fractions, a saponified fraction which represents 99% and is characterized by the presence of a high amount of unsaturated fatty acids such as oleic acid (45-50%) and linoleic acid (30-35%) (El Kharrassi et al, 2018;Zaaboul et al, 2018). While, the unsaponified fraction represents 1% and is formed by chemical components such as polyphenols, sterols, and tocopherols (Charrouf and Guillaume, 2008).…”
mentioning
confidence: 99%